(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Scientists and neuroscientists have recently conducted scientific and neurological research to discover what is behind the beauty and power of artwork in conveying its meaning to its audience. Philosophers have studied black boxes for years and researchers have delved into them lately. In this regard, the present study was conducted to investigate the impact of beauty when facing familiar and unfamiliar works of art. Aesthetics is one of the most important and controversial factors in the history of art and its influence cannot be ignored. Various methodologies of the mind process in the presence of art and aesthetics were discussed for this purpose. The present article has tried to follow up on the origin of beauty in the perceiver by looking at a beautiful phenomenon and by adopting three biological, cognitive, and psychological perspectives and achieve a relatively comprehensive view of beauty and its place in the process of human perception. Based on this, aesthetic pleasure is not only limited to the sense of sight and the external appearance of the city, but it is the result of the effect of all design purposes on the human senses.